2010
DOI: 10.1590/s1413-86702010000500017
|View full text |Cite
|
Sign up to set email alerts
|

Response predictors to treatment with pegylated interferon in chronic hepatitis B

Abstract: The clinical and epidemiological importance of chronic B hepatitis is currently unquestionable as a cause of end-stage liver disease and hepatocellular carcinoma. Recently, predictors of treatment response of this disease have been studied, both before and during the course of medication. Therapy stopping rules have been proposed, which may be useful in patients presenting poor treatment tolerance. This review discusses the treatment response predictors usefulness, with emphasis on ALT, quantitative HBsAg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
1
1
0
1
Order By: Relevance
“…Our study demonstrated that expression of IFNR2 protein had a close correlation with hepatic inflammation. Moreover, the majority of responders with chronic hepatitis B exhibited a high level of IFNR2 protein expression prior to treatment, which conforms to other previous studies [24][25]. To the best of our knowledge, this is the first study performed in China to determine both viral genotype and expression level of host IFNR2 that are closely correlated with the response to Peg-IFN-α-2a therapy in patients with chronic hepatitis B disease.…”
Section: Discussionsupporting
confidence: 88%
“…Our study demonstrated that expression of IFNR2 protein had a close correlation with hepatic inflammation. Moreover, the majority of responders with chronic hepatitis B exhibited a high level of IFNR2 protein expression prior to treatment, which conforms to other previous studies [24][25]. To the best of our knowledge, this is the first study performed in China to determine both viral genotype and expression level of host IFNR2 that are closely correlated with the response to Peg-IFN-α-2a therapy in patients with chronic hepatitis B disease.…”
Section: Discussionsupporting
confidence: 88%
“…Современная технология иммобили-зации активного белка с полиýтиленгликолем с помощью ýлектронно-лучевого синтеза модифи-цирует фармакокинетические характеристики соединения, позволяя создавать лекарственные препараты с высокой терапевтической активно-стью и низкой токсичностью [16][17][18]. Результа-том такой модификации является возрастание биодоступности ИФН, снижение колебаний уров-ня активного вещества в крови, более длительное сохранение ýффективной концентрации в орга-нах-мишенях, что и увеличивает ýффективность интерферонотерапии [8,10,[19][20][21][22]. Уникальность препарата ИФН α-2b, иммобилизированного на полиýтиленгликоле с помощью ýлектронно-луче-вого синтеза, заключается в защите белковой мо-лекулы от действия протеолитических ферментов ЖКТ, благодаря чему появляется возможность перорального применения лекарственного препа-рата на основе иммобилизированного ИФН α-2b.…”
Section: Discussionunclassified
“…2,3,7,8 Genotyping of HBV is essential to detect patients who are highly likely to respond to interferon or pegylated interferon. 9,10 The primary mutation that confers resistance to the nucleoside analog lamivudine is rtM204V/I, which is located in the tyrosinemethionine-aspartate-aspartate (YMDD) motif of the HBV DNA polymerase, and is often accompanied by the mutation rtL180M. HBV that carries rtM204I or rtM204V + rtL180M is also resistant to telbivudine in cell culture.…”
Section: Introductionmentioning
confidence: 99%